Preparation the antibacterial coatings based on natural mineral materials (International Journal of Biology and Chemistry, 2021)
The purpose of the study is to obtain nanofilms based on clay minerals and to study the antibacterial activity of the obtained nanocomposite coatings. Diatomite and kaolin were pretreated with sulfuric acid. Silicon plates were used as model substrates. For the first time, multilayers of the composition diatomite/PAA and kaolin/PAA were obtained by multilayer assembly. In the multi-layer, the antiseptic chlorhexidine was introduced, which plays the role of an antibacterial agent. Scanning electron microscopy (SEM) determined the distribution and thickness of the obtained multi-layers, the elemental composition of nanofilms was determined by the SEM-EDX method, the specific surface of natural and sulfuric acid-modified diatomite and kaolin was examined by the BET method, and the wetting angle was also determined by the lying drop method. Obtaining coatings on the surface of implantable systems is one of the promising areas in modern medicine. In this regard, the production of nanocovers with antibacterial properties is an urgent issue in the fight against infectious diseases associated with bacterial growth. One of the modern methods for producing nanofilms that are currently used is the Layer by Layer (LBL) method. Nanofilms obtained by this method have found application in tissue engineering and dressings. The peculiarity of this study is the use of clay minerals such as diatomite of the Mugodzharsky deposit and kaolin of the Alekseevsky deposit, which are concentrated in the west and north of Kazakhstan.The obtained multilayers were used as carriers for chlorhexidine and their antibacterial activity was studied. Nanofilms of diatomite/PAA/chlorhexidine and kaolin/PAA/chlorhexidine were tested against the E. Coli gram-negative bacterium. Thus, the obtained nanocomposite coatings based on kaolin and diatomite can be potential carriers for drugs.